Skarb z V okresu epoki brązu ze Strobina, gm. Konopnica w świetle badań metaloznawczych - Swat, Damian (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
The article is to describe the metal monuments discovered in position No. 2 in Strobin (commune Konopnica) in the light of metallurgical studies. This treasure dates back to the V Bronze Age by. A. Montelius (H B3 by P. Reinecke) and comes with a fortified settlement of the Lusatian culture. Article is divided into several parts. The first of these is explained differences and definitions related to metallurgical studies. In a further describes the main components of alloys made of tin bronzes. The main components of bronze alloy is tin and copper. It is also described how the amount of tin and copper affect the quality and mechanical properties of the alloy. There are also important alloying elements that reduce or increase the quality and strength of the alloy. The next section describe the metallurgical test methods such as X-ray that allows for finding the defects in the metal. Another method which allows to determine the chemical composition of the alloy is spectral analysis. The next section describes the analysis of metallurgy treasure discovered in Strobin in 1982. It contained fragments of pottery and bronze objects, such as sickles, bracelets, nodules, necklaces, rings, pendants and one bead. The last part is presented the summary and conclusions.